IMPROVED DATA DETECTION PROCESSES USING RETRAINING OVER TELEPHONE LINES (Journal of Engineering, 2009)
This paper describes two new developed detection processes for a modem over the publicswitched telephone network. The modem is a synchronous serial system using a 16-pointQAM signal with a detector. The detector is preceded by an adaptive filter that is adjustedto make the sampled impulse response of the channel and filter minimum phase. The ideaof these two new detectors is to transmit a known retraining data every specified intervaland make use of these known data to improve the conventional nonlinear equalizer andnear maximum likelihood detector.Results of computer simulation tests are presented comparing tolerance to additive whiteGaussian noise with retraining and with out retraining. The detectors with retrainingachieve a better noise performance than conventional detectors. Furthermore the amountof retraining data is varied to find the best compromise between efficiency of datatransmission and performance improvement